Pendampingan Pembuatan Sistem Informasi Pelayanan Pengaduan Masyarakat Berbasis Web di Desa Kalijaga Tengah - Rodiah, Rodhiah Filkhair; Maedani, Muhaffivin; Saiful, Muhammad; Juniarta, Adrian; Amri Muliawan Nur (Jurnal Teknologi Informasi untuk Masyarakat, 2024)
Managing public complaints is an important aspect in improving the quality of public services, especially as a means of bridging the needs and aspirations of the community to the government. However, in Kalijaga Tengah Village, Aikmel District, East Lombok Regency, the process of managing public complaints is still carried out manually, such as through oral submissions or written letters, which often faces various obstacles, including disorganized recording, difficulty tracking the status of complaints, and slow response. This can hinder efforts to improve public services and reduce the level of public trust in village government. To overcome these challenges, innovation is needed in the form of implementing  a web-based information system designed to increase efficiency, transparency and accuracy in managing public complaints. This information system allows the public to submit complaints online, monitor progress in handling complaints, and receive responses more quickly . On theother hand, village officials can manage complaint data in a structured manner, prioritize handling, and produce reports that support effective decision making. Apart from that, this system is expected to encourage active community participation in village governance, strengthen relations between the community and village government, and be the first step in the modernization of information technology-based administration. The implementation of this system not only aims to improve the quality of public services in Central Kalijaga Village, but also as a model for effective application of technology in the rural environment, which integrates traditional values ​​with modern technological innovation